ANALISIS PERENCANAAN PAJAK DALAM PERHITUNGAN PAJAK PENGHASILAN BADAN PADA PT. SINAR CIPTA PERSADA SEJATI - Kenju, Blandina Sefrida; Elim, Inggriani; Pusung, Rudy J (Universitas Sam Ratulangi, 2019)
Â The purpose of this study was to determine the application of tax planning in calculation the corporate income tax owed at PT. Sinar Cipta Persada Sejati. The results of this study are expected to be able to provide information and input to the company PT. Sinar Cipta Persada Sejati so that companies can carry out tax planning in an effort to calculation tax payments, but still in income tax legislation No. 36 of 2008. With the implementation of tax planning by the company, it can calculation the burden of corporate tax payable as much as Rp. 2,500,000.